Morphometric aspects of Scyllarides latus - ROMEO, T.; FLORIO, G.; LENTINI, F.; CASTRIOTA, L.; FALAUTANO, M.; CONSOLI, P.; PELUSI, P.; GRECO, S. (Mediterranean Marine Science, 2004)
The slipper lobster, Scyllarides latus (Latreille, 1803), is the only representative species of the genusScyllarides in the Mediterranean Sea. In this study, we examined some biological aspects of this species sampled in the Straits of Messina. The specimens were sexed, measured and weighed. The relationships between body measurements (length and width of the carapace, antennal length) and length-weight relationship were calculated. Furthermore, the correlation matrix (Pearson’s coefficient) was calculated. Two hundred specimens were collected, ranging in size from 81 to 305 mm in total length, and between 21 and 1490 g in weight. A rare juvenile of 39 mm CL was recorded. A sex ratio of 1:1 was found. The carapace length – weight relationship was almost isometric. The wide size range sampled and the presence of a juvenile, indicate an interesting habitat for studying the presence and growth of Scyllarides latus in the Straits of Messina.